Pengaruh Pemanfaatan Media Pembelajaran Interaktif Berbasis Android terhadap Motivasi Belajar PAI Siswa di MTs Negeri 4 Mandailing Natal - Putri Septiana Rizki; Syamsiah Depalina Siregar (Jurnal Pendidikan dan Humaniora Rumbio, 2026)
This study aims to determine the effect of the use of Android-based interactive learning media on Islamic Religious Education learning motivation in students at MTs Negeri 4 Mandailing Natal. The research method used is a pretest-posttest group design with a sampling system using cluster random sampling. The research subjects consisted of 3 classes, namely class 7a, 8d as experiments and 9b as controls. What was done in the two sample classes can be distinguished by the way the Android-based interactive learning media was used in the experimental class, while the control class was not. The instrument used was an explanatory test instrument. The results of the study showed that the t-test on learning outcomes obtained t count = 1.87 is greater than t table = 1.67 which is supported by the N-gain value of the experimental class of 0.74 compared to the control class. In addition, the results of the study the use of Android-based interactive learning media has an influence of 74.50% on student learning outcomes.